Density‐Controlled Freestanding Biodegradable Nanopillar Arrays Patterned via Block Copolymer Micelle Lithography. Issue 2 (22nd November 2016) - Lee, Gyeong Won; Lee, Seunghyun; Kim, Jang Hwan; Yim, Sang‐Gu; Ryu, Jooyeon; Lee, Eunji; Lee, Jaebeom; Yoo, Seong Il; Yang, Seung Yun
Abstract : Dimensionally well‐controlled biodegradable nanopillar arrays are successfully created by using density‐controlled block copolymer nanomasks by pH and anisotropic plasma etching on different substrates including flexible sheets. This approach can offer a feasible route to create nanostructures on various soft materials with dimensional controllability. Abstract : Vertically aligned polymer nanopillar arrays on substrates are receiving increasing interest as functional surfaces for a broad range of applications. However, methods for preparing polymeric nanopillar arrays have poor controllability of dimensional parameters and are limited to few polymers. Here, a new method to prepare freestanding biodegradable nanopillar arrays on different substrates, including flexible sheets, by plasma etching with polystyrene‐ block ‐poly(acrylic acid) (PS‐PAA) block copolymer (BCP) micelles encapsulating Au nanoparticles (AuNP@PS‐PAA) is reported. The adsorption density of the AuNP@PS‐PAA micelles is controlled by the pH of the micelle solutions, affecting electrostatic interaction with the polyelectrolyte layers formed on a poly(lactic‐ co ‐glycolic acid) (PLGA) film coated on the substrates; thus, density‐controlled PLGA nanopillar arrays are prepared using the micelle array as an etching mask during plasma etching. The height of the PLGA nanopillars is controlled by adjusting the plasma etching time, achieving high aspect ratios (>10) on inch‐sized substrates. This new platform combining bottom‐up (controlling absorption of BCP micelles used as etching mask) and top‐down (plasma etching for nanopillar formation) approaches can be applied to prepare nanopillar arrays on substrates using different soft materials including biodegradable polymers.